Prevalence, Causes, and Factors Associated with Visual Impairment and Blindness among Registered Pensioners in Ghana - Benjamin D. Nuertey; Kwesi Nyan Amissah-Arthur; Joyce Addai; Victor Adongo; Augustine D. Nuertey; Clement Kabutey; Isaac Asimadu Mensah; Richard Bekoe Biritwum (Journal of Ophthalmology)
Purpose. To determine the prevalence, causes, and factors associated with presenting visual impairment and blindness among pensioners. Design. A nationwide cross-sectional study. This study was part of the analysis on data obtained in the pensioners’ medical survey conducted among members of the National Pensioners Association in Ghana. Method. (i) Setting: it was a multicenter study involving thirteen centers throughout Ghana with a center in each regional capital. (ii) Study population: the study involved 4813 pensioners. (iii) Observation procedures: data were captured through the use of questionnaires, physical examinations including eye examinations, and urine and blood sample analysis. (iv) Main outcome measure: presenting visual impairment and blindness (as defined by the WHO ICD-10 classification). Results. The overall prevalence of blindness among pensioners in Ghana was 3.8% (95% CI = 3.2–4.4), while the prevalence of moderate and severe visual impairment was 21.7% (95% CI = 20.5–23.0). The prevalence of blindness was lowest in the 60–65-year-old age group (2.1% (95% CI = 1.3–2.8)) and highest in the above 80-year-old age group (12.2% (95% CI = 6.6–17.8)). Cataract was the leading cause of blindness (62.4%) and moderate and severe visual impairment (55.7%). Factors significantly associated with blindness and visual impairment include educational status, vegetarianism, arthritis, and having proteins in urine. Conclusion. There is a high prevalence of visual impairment and blindness among the pensioners in Ghana. Sadly, the greatest cause was cataract, which is correctable. Increase in formal education status will be important in the prevention of blindness and visual impairment.